A Formal Interactive Verification Environment for the Plan Execution Interchange Language (2012)
The Plan Execution Interchange Language (PLEXIL) is an open source synchronous language developed by NASA for commanding and monitoring autonomous systems. This paper reports the development of the PLEXIL’s Formal Interactive Verification Environment (PLEXIL5), a graphical interface to the formal executable semantics of PLEXIL. Among its main features, PLEXIL5 provides model checking of plans with support for formula editing and visualization of counterexamples, interactive simulation of plans at different granularity levels, and random initialization of external environment variables. The formal verification capabilities of PLEXIL5 are illustrated by means of a human-automation interaction model.